Chicago Paper - Correlation of Formations of Huronian Group in Michigan (with Discussion) - R. C. Allen (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
About four years ago the writer proposed a revision of the correlation of the Huronian formations in Michigan, and noted the bearing of the question on the correlations of the Huronian rocks in Wisconsin and Minnesota.1 Dr. C. K. Leith opposed this revision and argued for the retention of the correlations of the United States Geological Survey, published in 1911,2 for which he and Dr. Van Hise were mainly responsible. As late as June, 1917, Harder and Johnson, following Leith, thought it "premature to change radically a correlation based on years of careful field work."3 The work of Wolff on the Mesabi and Cuyuna Ranges, of Hotchkiss on the Gogebic Range (unpublished), and of the writer and assistants on the Michigan ranges, together with data developed by exploratory and mining operations, has introduced so many new facts not recognized in the scheme of the U. S. Geological Survey that the correlations of 1911 must be considered, in some important respects, obsolete. Indeed, new data are accumulating so rapidly that any classification, which for the moment may seem best to explain the facts, is almost immediately modified or refined by further observations. The problem of Huronian correlations is difficult, but interesting and important. With the aid of fossils, stratigraphers of the post-Algonkian formations have been able to show that slight disconformities mag separate strata of vastly different ages, and that within physically conformable strata may be concealed a hiatus of great magnitude. In the non-fossiliferous Huronian group, minor physical breaks in the strata are only beginning to attract attention, and it is too early to discuss what bearing these will have in correlating the formations of one area with those of another, but it is safe to say that the "lost intervals" which are not disclosed by physical relationships will remain forever lost; therefore we may not hope to discover the ultimate truth concerning the